A (TiC+Ti) / Mg layered composite material and preparation method thereof

The layered porous (TiC+Ti) ceramic skeleton was prepared by frozen casting and in-situ sintering, and the layered structure (TiC+Ti)/Mg composite was formed by air pressure impregnation, which solved the problem of insufficient toughness of magnesium-based composite materials with high ceramic content, and achieved comprehensive performance of high strength, high toughness and high wear resistance.

CN116904795BActive Publication Date: 2025-04-11GUIZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310767527.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-27
Publication Date
2025-04-11
Estimated Expiration
2043-06-27

AI Technical Summary

Technical Problem

The lack of toughness of high-ceramic content magnesium-based composites limits their use in high-strength and toughness applications.

Method used

Laminated porous (TiC+Ti) ceramic skeletons were prepared by frozen casting and in-situ sintering, and the magnesium alloy was completely immersed in the ceramic skeleton by air pressure impregnation to form a layered structure (TiC+Ti)/Mg composite.

Benefits of technology

By regulating the ratio of TiC and Ti, the composite material achieves comprehensive mechanical properties of high strength, high toughness and high wear resistance, and has good damping performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116904795B_ABST
    Figure CN116904795B_ABST
Patent Text Reader

Abstract

The present invention discloses a (TiC+Ti) / Mg layered composite material and a preparation method thereof. The preparation method of the composite material comprises the following steps: a layered porous TiC ceramic skeleton is prepared by freeze casting and in-situ generation, and a magnesium alloy is completely immersed in the ceramic skeleton by gas pressure infiltration to obtain a layered (TiC+Ti) / Mg composite material. Benefiting from the various toughening mechanisms such as multi-crack extension, crack passivation and deflection, and pull-out of metal layers and ceramic sheets caused by the layered structure, the composite material has good compressive strength, flexural strength, tensile strength, fracture toughness, wear resistance and damping performance. The composite material is expected to be applied to aerospace, automobile, communication and other fields that have a large demand for high-performance lightweight wear-resistant materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to the technical field of magnesium-based composite materials, and in particular to a (TiC+Ti) / Mg layered composite material and a preparation method thereof. Background technology:

[0002] Magnesium and its magnesium alloys are one of the lightest structural materials with high specific strength, specific stiffness, good dimensional stability, vibration reduction, anti-electromagnetic interference and shielding properties. They are increasingly valued in the fields of aerospace, automobiles, communications, electronics, etc. However, its low absolute strength, limited plasticity and insufficient stiffness limit its application range. In recent years, people have improved its comprehensive properties by introducing reinforcing phases into Mg and its alloys. Studies have shown that when an appropriate amount of hard ceramic particles are added, the strength of magnesium and its alloys is improved. However, when the content of ceramic particles is too high, the toughness of magnesium-based composites decreases sharply, which is not conducive to the preparation of high-strength and toughness magnesium-based composites and limits the application of high-ceramic content magnesium-based composites. Therefore, it is necessary to seek a new method to adjust the reinforcement relationship between ceramic particles and aluminum matrix, so as to solve the problem of high strength and toughness matching of ceramic particle reinforced magnesium-based composites.

[0003] With the development of bionic materials, a promising method to solve this problem is provided - shell-like structure. It is found that the nacre composed of brittle minerals (95 vol%) and a small amount of biopolymers (5 vol%) exhibits unprecedented strength and fracture toughness at least one order of magnitude higher than its components, which can be attributed to its complex "brick and mud" layered structure. A large number of studies have shown that metal-based composites with high ceramic content (20-30 vol%) that mimic the structure of shell nacre have good strength and toughness. Among the many methods of mimicking shell structures, "freeze casting" has gained more and more attention due to its advantages such as simple operation, low cost, and adjustable microstructure of porous materials. In recent years, scholars at home and abroad have begun to apply freeze casting to prepare magnesium-based shell-like materials. Among the many ceramic particle reinforcement phases, TiC has the advantages of high hardness, high melting point and excellent wear resistance. These advantages make it a very advantageous reinforcement phase in magnesium-based composites with shell-like structure, and there are few reports on the preparation of (TiC+Ti) / Mg layered composites by freeze casting and melt infiltration. The invention adopts a certain proportion of TiH2 and graphite powder to prepare a layered porous preform by freeze casting, synthesizes Ti and TiC by in-situ sintering, and obtains Ti and TiC in different proportions by adjusting the ratio of TiH2 and graphite powder, and then infiltrates the preform with magnesium melt to obtain a (TiC+Ti) / Mg layered composite material. The composite material can have comprehensive mechanical properties of high strength, high toughness and high wear resistance by adjusting the ratio of TiC and Ti generated by the reaction, and also has good damping performance. Summary of the invention:

[0004] The present invention solves the problem of poor toughness of magnesium-based composite materials with high ceramic content, and provides a (TiC+Ti) / Mg layered composite material and a preparation method thereof. The present invention benefits from multiple toughening mechanisms caused by the layered structure, and the ratio of TiC and Ti generated by the reaction is adjusted to make the composite material have good mechanical properties. The composite material can be applied to aerospace, automobile, communication and other fields that have a large demand for high-performance lightweight structural materials.

[0005] The invention provides a method for preparing a (TiC+Ti) / Mg layered composite material, comprising the following steps: freezing a slurry consisting of TiH2 powder, graphite powder, ammonium polyacrylate and neutral silica sol using a unidirectional freezing mold, preparing (TiC+Ti) porous ceramic skeletons with different proportions by adjusting the ratio of TiH2 and graphite powder through in-situ sintering, and completely immersing a magnesium matrix into the porous ceramic skeleton through gas pressure infiltration to obtain a layered structure (TiC+Ti) / Mg composite material.

[0006] During the infiltration process, the ceramic layers of the porous ceramic skeleton remain basically intact, while the interlayer pores are completely filled with molten magnesium alloy to form a layered structure. The composite material can be given good strength and toughness by regulating the ratio of TiC and Ti generated by the reaction.

[0007] Preferably, the preparation method specifically comprises the following steps:

[0008] (1) Powder mixing: Pour TiH2 powder and graphite powder into a container, add water, ammonium polyacrylate and neutral silica sol, fill with high-purity argon gas, and ball mill for 1-3 hours to obtain a slurry with uniformly dispersed particles;

[0009] (2) Freezing: placing the one-way freezing mold in a freezing container at -30°C to (-35°C), then pouring the slurry obtained in step (1) into the freezing container and freezing for 1.0 to 1.5 hours, and after demolding, obtaining a block with ceramic layers and ice layers arranged alternately;

[0010] (3) Low temperature drying: Dry the green body in a low temperature dryer for 24-48 hours to obtain a dry green body;

[0011] (4) Sintering: Sintering the green body under the protection of an inert gas to obtain a layered porous ceramic skeleton;

[0012] (5) Infiltration: The layered porous ceramic skeleton and the magnesium alloy are placed in a graphite mold in turn, and then the mold is placed in a vacuum reaction vessel. First, the vacuum is evacuated to below 10Pa at room temperature, and the temperature is raised to 750℃-850℃ and kept warm. Then, high-purity argon gas is introduced into the vacuum furnace to allow the metal liquid to infiltrate the ceramic skeleton to obtain a layered structure (TiC+Ti) / Mg composite material.

[0013] The present invention adopts freeze casting and in-situ generation methods to prepare a layered porous (TiC+Ti) ceramic skeleton, and combines gas pressure infiltration to completely immerse the magnesium alloy into the ceramic skeleton to obtain a layered (TiC+Ti) / Mg composite material.

[0014] Preferably, the one-way freezing mold comprises a constant temperature freezing container, a heat-conducting liquid and a metal column are arranged at the bottom of the constant temperature freezing container, the metal column is immersed in the heat-conducting liquid, a metal plate is arranged on the top of the metal column, and a polytetrafluoroethylene tube for placing the slurry is arranged on the top of the metal plate.

[0015] More preferably, the heat-conducting liquid is alcohol, and the metal column and the metal plate are made of copper. The constant-temperature freezing container is a constant-temperature freezer.

[0016] Preferably, the specific steps of step (1) are: pouring a certain proportion of TiH2 powder and graphite powder into a ball mill, adding water, ammonium polyacrylate and neutral silica sol, filling with high-purity argon and ball milling for 2 hours to obtain a slurry with uniformly dispersed particles. The conditions of low-temperature drying described in step (3) are low temperature (i.e. temperature <-60°C) and low pressure (i.e. pressure <10Pa).

[0017] Preferably, the total volume of the TiH2 powder and graphite powder in step (1) accounts for 20%-50% of the total volume of the slurry, the ammonium polyacrylate accounts for 1%-1.5% of the total volume of the slurry, and the neutral silica sol accounts for 0.8%-1% of the total volume of the slurry. Further preferably, the total volume of the TiH2 powder and graphite powder accounts for 28%-30% of the total volume of the water-based slurry.

[0018] Preferably, the mass ratio of the TiH2 powder to the graphite powder is 4-8: 1. Further preferably, the mass ratio of the TiH2 powder to the graphite powder is 30-35:6 (5:1-35:6).

[0019] Preferably, the specific steps of step (4) are: first, the green body after low-temperature drying is placed in a vacuum sintering furnace, and then the air in the sintering furnace is extracted, and when the vacuum gauge value reaches below -0.1MPa, an inert gas with a purity of 99.9% is continuously introduced into the vacuum furnace, the gas pressure is maintained at 0MPa, and atmospheric sintering is performed, the temperature is increased at a rate of 8-12°C / min, and the temperature is kept at 500°C for 25-35 minutes, 1000°C for 0.8-1.2 hours, and 1500°C for 1-1.5 hours, and finally the temperature is reduced to 300°C at a cooling rate of 8-12°C / min and then cooled with the furnace to obtain a layered porous ceramic skeleton. The inert gas is argon.

[0020] Preferably, the mass ratio of the layered porous ceramic skeleton and the magnesium alloy in step (5) is 3:7-8.

[0021] The present invention also protects the (TiC+Ti) / Mg layered composite material obtained by the above preparation method. The ceramic content of the composite material is 28%-50%.

[0022] The present invention also protects the application of the (TiC+Ti) / Mg layered composite material in the fields of aerospace, automobile or communication.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] (1) Compared with existing layered composite materials, the present invention adopts an environmentally friendly freeze-casting method to construct a ceramic skeleton. The lamellar morphology of the ceramic skeleton can be controlled by adjusting factors such as freezing temperature, additives, ceramic content, powder particle size and sintering temperature, thereby regulating the comprehensive performance of the composite material to meet the material selection requirements under various working conditions.

[0025] (2) The present invention benefits from multiple toughening mechanisms caused by the layered structure, such as multiple crack extension, crack passivation and deflection, and pull-out of metal layers and ceramic sheets. By regulating the ratio of TiC and Ti generated by the reaction, the composite material has excellent compressive strength, flexural strength, tensile strength and fracture toughness, and has good wear resistance and damping properties.

[0026] (3) The present invention adopts in-situ self-generated technology to prepare the ceramic skeleton of TiC+Ti. Compared with other methods, the in-situ self-generated reinforcement has good interface bonding and wettability with the matrix, so that the metal matrix composite material has excellent and stable performance. The reaction equation is as follows:

[0027] TiH2→Ti+H2; Ti+C→TiC

[0028] The decomposition process of TiH2 occurs in the range of 620℃~720℃. Because the Ti obtained by decomposition is highly active, it is easy to react with graphite powder to generate TiC when kept at 1500℃ for 1-1.5h. When too much TiH2 is added, the decomposed Ti will wrap and bond the TiC particles generated by the reaction, which not only improves the wettability of the ceramic skeleton and the magnesium alloy, but also enhances the strength of the ceramic skeleton, ultimately leading to an improvement in the fracture toughness of the composite material. Description of the drawings:

[0029] Figure 1 It is a process flow chart of the preparation of the (TiC+Ti) / Mg layered composite material of the present invention.

[0030] Figure 2 It is a structural schematic diagram of the one-way freezing mold proposed by the present invention.

[0031] Figure 3It is the fracture microscopic morphology of the ceramic skeleton after sintering in step (4) of Example 1, wherein (a) is the longitudinal fracture and (b) is the transverse fracture.

[0032] Figure 4 This is the XRD diagram of the (TiC+Ti) / Mg layered composite material prepared in Example 1.

[0033] Figure 5 OM diagram of the (TiC+Ti) / Mg layered composite material prepared in Example 1, wherein (a) is a longitudinal fracture and (b) is a transverse fracture.

[0034] Figure 6 Schematic diagram of the structure of the sample undergoing mechanical testing, where (a) is a bending test and (b) is a fracture test.

[0035] Figure 7 It is the dimension drawing of tensile specimen.

[0036] Figure 8 It is the damping-strain curve of AZ91D magnesium alloy and the prepared composite material.

[0037] Explanation of the accompanying drawings: 1. Constant temperature freezer; 2. Polytetrafluoroethylene tube; 3. Slurry; 4. Copper plate; 5. Copper column; 6. Alcohol. Specific implementation method:

[0038] The following examples are provided to further illustrate the present invention, rather than to limit the present invention.

[0039] Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the experimental materials and reagents herein are conventional commercial products in the art.

[0040] The one-way freezing mold used in the following embodiments comprises a constant temperature freezing container, a heat-conducting liquid and a metal column are arranged at the bottom of the constant temperature freezing container, the metal column is immersed in the heat-conducting liquid, a metal plate is arranged on the top of the metal column, and a polytetrafluoroethylene tube 2 for placing slurry 3 is arranged on the top of the metal plate. In the present invention, the heat-conducting liquid is preferably alcohol 6, the metal in the metal plate and the metal column is a heat-conducting metal, the metal plate is preferably a copper plate 4, the metal column is a copper column 5, and the constant temperature freezing container is a constant temperature freezer 1.

[0041] The heat in the slurry in the one-way freezing mold proposed by the present invention is transferred to the copper column 5 through the copper plate 4, and the alcohol 6 accelerates the heat conduction. The temperature difference between the upper and lower parts of the copper plate 4 forms a vertical temperature gradient. When in use, the mold is first frozen to -30°C-(-35°C), and the slurry 3 is placed in the polytetrafluoroethylene tube 2. The copper plate 4 and the copper column 5 are connected, and together with the alcohol 6, they form a heat conduction module to form a one-way temperature gradient.

[0042] The materials used in the following examples include TiH2 powder, graphite powder, ammonium polyacrylate, neutral silica sol, deionized water and magnesium alloy, and the specific information is shown in Table 1.

[0043] Table 1 Specific information of materials used

[0044]

[0045]

[0046] Example 1

[0047] A method for preparing a (TiC+Ti) / Mg layered composite material comprises the following steps:

[0048] (1) Powder mixing: Weigh 25 g TiH2 powder and 6 g graphite powder into a ball mill, add 22 mL deionized water, 0.3 g ammonium polyacrylate and 0.2 g neutral silica sol, and then fill with high-purity argon and ball mill for 2 hours.

[0049] (2) Freezing: First, place the one-way freezing mold ( Figure 2 ) is placed in a refrigerator at -35°C for 30 minutes, then the stirred slurry is poured in and frozen for 1 hour, and after demolding, a block with alternating ceramic layers and ice layers is obtained.

[0050] (3) Low-temperature drying: Place the block into a freeze-drying device and perform freeze-drying in a low-temperature, low-pressure (<-65°C, <10Pa) environment for 48 hours.

[0051] (4) Sintering: First, place the green body into a vacuum sintering furnace, then evacuate the air in the sintering furnace, and when the vacuum gauge value reaches below -0.1MPa, continue to introduce argon gas with a purity of 99.9% into the vacuum furnace, maintain the gas pressure at 0MPa, and perform atmospheric sintering. The sintering curve is: heating at a rate of 8°C / min, keeping at 500°C for 30 minutes, 1000°C for 1 hour, and 1500°C for 1.2 hours, and finally cooling the temperature to 100°C at a cooling rate of 8°C / min and then cooling with the furnace, and finally obtaining a porous ceramic skeleton with a certain strength.

[0052] (5) Infiltration: Place the porous ceramic skeleton and magnesium alloy with a mass ratio of 3:7 into the graphite mold in turn, and place the mold into a vacuum furnace. First, evacuate to below 10Pa at room temperature, heat to 800℃ at 5℃ / min, and keep warm for 15 minutes. Then introduce high-purity argon gas into the vacuum furnace to form high pressure above the molten metal liquid, while the internal pores of the ceramic skeleton below are still in a vacuum state. The internal and external pressure difference is used to make the metal liquid infiltrate into the ceramic skeleton. Keep warm and pressure for 5 minutes, and then cool to room temperature at 10℃ / min to obtain a (TiC+Ti) / Mg layered composite material.

[0053] The prepared composite material was cut and polished, and performance tests and microscopic morphology observations were performed:

[0054] (1) Mechanical properties: The composite material was cut into specimens of different sizes using an EDM wire cutting machine. In compression and bending, the specimen sizes were 4 mm × 4 mm × 8 mm and 3 mm × 4 mm × 20 mm, respectively. The specimen for the fracture toughness test was 2 mm × 4 mm × 22 mm. A notch was opened in the middle of the specimen with a notch width of 0.3 mm and a notch depth of 2 mm. Figure 6 The tensile specimen is a sheet specimen of 140mm×20mm×10mm (such as Figure 7 ). The compression, bending, tension and fracture tests of the composite materials were carried out using INSTRON3369 electronic universal materials testing machine.

[0055] All samples were ground and polished before testing. The loading rate of compression test was 0.5 mm / min. The loading rate of bending and fracture was 0.1 mm / min, and the test span was 10 mm.

[0056] Compressive strength (σ C ) and flexural strength (σ f ) is calculated according to the following formula:

[0057]

[0058]

[0059] Where P IC is the maximum applied load, A is the cross-sectional area of ​​the compression specimen, S is the span, b is the specimen width, and h is the specimen thickness.

[0060] The crack initiation toughness (K IC ):

[0061]

[0062]

[0063] P IC is the maximum load when the sample breaks; a is the notch depth; S is the support span; B is the specimen thickness, and W is the specimen width.

[0064] (2) Friction and wear properties: The composite material was cut into 10 mm × 10 mm × 5 mm cuboids using an electric spark wire cutting machine. Linear reciprocating friction and wear tests were carried out on the cross section (TS) and longitudinal section (LS) for 20 min. Wear tests were carried out on the longitudinal section (LS) in the direction parallel to the lamellar growth (hereinafter referred to as LS-P) and perpendicular to the lamellar growth (hereinafter referred to as LS-V). The load applied in the experiment was 10 N, and the linear reciprocating distance and speed were 5 mm and 8 mm / s, respectively.

[0065] The wear rate can be calculated by the following formula:

[0066]

[0067] Where A is the wear cross-sectional area, L is the wear length, F is the load, and S is the sliding distance.

[0068] (3) Damping performance: The damping performance of the sample was tested using a DMAQ850 dynamic thermal mechanical analyzer at room temperature with a frequency of 1 Hz and a sample size of 30 mm × 3 mm × 1 mm.

[0069] (4) Micromorphology: The micromorphology of the porous ceramic skeleton was observed using a SUPRA55 scanning electron microscope produced by the German ZEISS company: a parallel and orderly layered structure was observed on the longitudinal section parallel to the temperature gradient ( Figure 3 .a), while the lamellae are observed to have a locally ordered but overall disordered morphology in cross section ( Figure 3 .b); X-ray diffractometer (XRD; BrukerAXS) was used to analyze the phase composition of (TiC+Ti) / Mg layered composite materials, with a diffraction angle range of 20-80° and a scanning speed of 5° / min. The results show that ( Figure 4 ): In the XRD spectrum of the composite material, TiC, Mg and Mg 17 Al 12 The diffraction peaks of the samples indicate that TiC was synthesized in situ and that no other impurities were present in the prepared composite material. The metallographic structure of the samples was observed using an XD30M series metallographic optical microscope produced by Ningbo Sunny Optical Instruments Co., Ltd. The white part is magnesium alloy, the dark gray part is ceramic sheet, and the metal layer and ceramic layer are parallel and orderly arranged alternately in the longitudinal section ( Figure 5 .a), while the lamellae on the cross section are locally ordered but globally disordered ( Figure 5 .b).

[0070] The test results of the ceramic content, compressive strength, flexural strength, tensile strength and fracture toughness of the composite material are shown in Table 2. Figure 8 shown.

[0071] Example 2

[0072] Same as Example 1, except that:

[0073] Step (1) was changed to: weigh 36 g TiH2 powder and 6 g graphite powder into a ball mill, add 26 mL deionized water, 0.32 g ammonium polyacrylate and 0.22 g neutral silica sol, and then fill with high-purity argon and ball mill for 2 hours.

[0074] Consistent with the test method of Example 1, the prepared composite material was cut and polished, and mechanical properties tests and microscopic morphology observations were performed. The test results of the ceramic content, compressive strength, flexural strength, tensile strength and fracture toughness of the composite material are shown in Table 2. Figure 8 shown.

[0075] Example 3

[0076] Same as Example 1, except that:

[0077] Step (1) was changed to: 48 g TiH2 powder and 6 g graphite powder were weighed and poured into a ball mill, and then 33 mL deionized water, 0.35 g ammonium polyacrylate and 0.24 g neutral silica sol were added, and then filled with high-purity argon and ball milled for 2 hours.

[0078] Consistent with the test method of Example 1, the prepared composite material was cut and polished, and mechanical properties tests and microscopic morphology observations were performed. The test results of the ceramic content, compressive strength, flexural strength, tensile strength and fracture toughness of the composite material are shown in Table 2. Figure 8 shown.

[0079] Example 4

[0080] Same as Example 1, except that:

[0081] Step (1) was changed to: 48 g TiH2 powder and 1 g graphite powder were weighed and poured into a ball mill, and then 33 mL deionized water, 0.35 g ammonium polyacrylate and 0.24 g neutral silica sol were added, and then filled with high-purity argon and ball milled for 2 hours.

[0082] The prepared composite material was cut and polished, and mechanical properties and microscopic morphology were tested in accordance with the test method of Example 1. The test results of the ceramic content, compressive strength, flexural strength, tensile strength and fracture toughness of the composite material are shown in Table 2.

[0083] Example 5

[0084] Same as Example 1, except that:

[0085] Step (1) was changed to: weigh 25 g TiH2 powder and 6 g graphite powder into a ball mill, add 9.64 mL deionized water, 0.3 g ammonium polyacrylate and 0.2 g neutral silica sol, and then fill with high-purity argon and ball mill for 2 hours.

[0086] The prepared composite material was cut and polished, and mechanical properties and microscopic morphology were tested in accordance with the test method of Example 1. The test results of the ceramic content, compressive strength, flexural strength, tensile strength and fracture toughness of the composite material are shown in Table 2.

[0087] Example 6

[0088] Same as Example 3, except that:

[0089] Change step (2) to: First, place the one-way freezing mold ( Figure 2 ) was placed in a refrigerator at -30°C for 30 minutes, then the stirred slurry was poured in and frozen for 1 hour, and after demolding, a block with alternating ceramic layers and ice layers was obtained.

[0090] The prepared composite material was cut and polished, and mechanical properties and microscopic morphology were tested in accordance with the test method of Example 1. The test results of the ceramic content, compressive strength, flexural strength, tensile strength and fracture toughness of the composite material are shown in Table 2.

[0091] Example 7

[0092] Same as Example 3, except that:

[0093] The sintering curve in step (4) was changed to: heating at a rate of 10°C / min, keeping at 500°C for 30 minutes, 1000°C for 1 hour, and 1500°C for 1.5 hours, and finally reducing the temperature to 500°C at a cooling rate of 10°C / min and then cooling in the furnace.

[0094] The prepared composite material was cut and polished, and mechanical properties and microscopic morphology were tested in accordance with the test method of Example 1. The test results of the ceramic content, compressive strength, flexural strength, tensile strength and fracture toughness of the composite material are shown in Table 2.

[0095] Comparative Example 1

[0096] The magnesium alloy is treated, comprising the following steps:

[0097] Weigh 200g of magnesium alloy (AZ91D) and put it into a graphite mold, and then put the mold into a vacuum furnace. First, evacuate to below 10Pa at room temperature, heat to 800℃ at 5℃ / min, and keep warm for 15min. Then, introduce high-purity argon gas into the vacuum furnace, keep warm and pressurized for 5min, and then cool to room temperature at 10℃ / min.

[0098] The prepared material was cut and polished, and mechanical properties and microscopic morphology were tested in accordance with the test method of Example 1. The test results of the ceramic content, compressive strength, flexural strength, tensile strength and fracture toughness of the composite material are shown in Table 2.

[0099] Comparative Example 2

[0100] A method for preparing a non-layered (TiC+C) / Mg composite material comprises the following steps:

[0101] Weigh 35g TiH2 powder and 6g graphite powder into a ball mill and mill for 2 hours. Then press the mixed powder and sinter it. The mixing and sintering of the powders are carried out under the protection of high-purity argon. Then preheat the prefabricated block at 300℃ for 30 minutes, add it into 300g magnesium alloy (AZ91D) melt, keep it warm and stir it to make the prefabricated block melt and disperse it in the magnesium melt, then refine, keep it warm and let it stand, and pour it to prepare a non-layered (TiC+C) particle reinforced magnesium-based composite material.

[0102] The prepared composite material was cut and polished, and mechanical properties and microscopic morphology were tested in accordance with the test method of Example 1. The test results of the ceramic content, compressive strength, flexural strength, tensile strength and fracture toughness of the composite material are shown in Table 2.

[0103] Table 2 Performance test results

[0104]

[0105]

[0106] From the test results, the (TiC+Ti) / Mg layered composite material with a ceramic content of 30% (Example 3) has the best flexural strength. The difference in performance can be attributed to: when the added TiH2 is sufficient, the full reaction of TiH2 and graphite powder is guaranteed, and more TiC ceramic reinforcement phases are synthesized in situ, and the reinforcement phases play an effective supporting and anti-friction role, thereby improving the compressive strength, flexural strength and wear resistance of the composite material, especially when the ceramic content reaches 50%, its compressive strength is the highest and the wear rate is the lowest (Example 5). When the added TiH2 is excessive, the remaining Ti in the reaction will wrap and bond the TiC particles generated by the reaction, improve the wettability of the ceramic skeleton and the magnesium alloy, and help reduce the infiltration defects in the composite material, thereby improving its fracture toughness. Especially when the Ti content is extremely high, its tensile strength and fracture toughness are the best (Example 4). Compared with Example 6, the lower freezing temperature can obtain a finer ceramic layer, which enhances the compressive strength, flexural strength and fracture toughness of the material. Compared with Example 7, the slow heating can prevent the deformation of the ceramic sheet layer and ensure that the various mechanisms of the layered structure can play a toughening role. Compared with the magnesium alloy matrix (Comparative Example 1) treated with the same process, the compressive strength, flexural strength, tensile strength and fracture toughness of the present invention are greatly improved. In Comparative Example 2, a non-layered (TiC+C) / Mg composite material was prepared by a stirring method. After testing, it was found that the compressive strength, flexural strength, tensile strength, fracture toughness and wear resistance of the layered composite material with high ceramic content of the present invention are better than those of the non-layered (TiC+Al) / Mg composite material with low ceramic content, reflecting the advantages of the shell-like layered structure.

[0107] Among metal materials, pure magnesium exhibits excellent damping performance, but its poor mechanical properties hinder its application. Therefore, it is necessary to explore a method to improve the mechanical properties of magnesium alloys while ensuring good damping performance. The present invention provides a way to achieve this goal - (TiC+Ti) / Mg layered composite material. From the damping-strain diagram ( Figure 8 ), in the strain amplitude independent stage, the damping performance of Examples 1-3 and Comparative Example 1 is almost the same, while in the strain amplitude dependent stage, the damping performance of Comparative Example 1 is more improved than that of Examples 1-3, while the critical strain amplitude of Examples 1-3 is higher than that of Comparative Example 1, and the damping performance of Examples 1-3 is almost the same. This shows that under low strain (0.1%), the composite material has higher strength than magnesium alloy and also has excellent damping performance.

[0108] In summary, the present invention benefits from a variety of toughening mechanisms such as multi-crack extension, crack passivation and deflection, and pull-out of metal layers and ceramic sheets caused by the layered structure. By regulating the ratio of TiC and Ti generated by the reaction, the present invention has good compressive strength, bending strength, tensile strength and fracture toughness. Its strength is greatly improved relative to the magnesium alloy matrix, while maintaining excellent fracture toughness, wear resistance and damping properties. The composite material is expected to be used in aerospace, new energy vehicles, electronic communications and other fields that have a large demand for high-performance, lightweight and wear-resistant materials.

[0109] The description of the above embodiments is only used to help understand the technical solution and core ideas of the present invention. It should be pointed out that for technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. These improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a (TiC+Ti) / Mg layered composite material, characterized in that: The specific steps include: (1) Mixing powder: Pour TiH2 powder and graphite powder into a container, add water, ammonium polyacrylate and neutral silica sol, fill with high-purity argon gas, and ball mill for 1-3 hours to obtain a slurry with uniformly dispersed particles. The mass ratio of the TiH2 powder to the graphite powder is 4-8:1; (2) Freezing: placing the one-way freezing mold in a freezing container at -30°C to (-35°C), then pouring the slurry obtained in step (1) into the freezing container and freezing for 1.0-1.5 hours, and after demolding, obtaining a block with alternating ceramic layers and ice layers; the one-way freezing mold comprises a constant temperature freezing container, a heat-conducting liquid and a metal column are arranged at the bottom of the constant temperature freezing container, the metal column is immersed in the heat-conducting liquid, a metal plate is arranged on the top of the metal column, a polytetrafluoroethylene tube for placing the slurry is arranged on the top of the metal plate, the heat-conducting liquid is alcohol, and the metal column and the metal plate are made of copper; (3) Low temperature drying: Dry the green body in a low temperature dryer for 24-48 hours to obtain a dry green body; (4) Sintering: Sintering the green body under the protection of inert gas to obtain a layered (TiC+Ti) porous ceramic skeleton; (5) Infiltration: The layered (TiC+Ti) porous ceramic skeleton and magnesium alloy are placed in the mold in sequence. The mold is then placed in a vacuum reaction vessel. The vacuum is first evacuated to below 10 Pa at room temperature, and the temperature is raised to 750°C-850°C and kept warm. High-purity argon gas is then introduced into the vacuum furnace to allow the metal liquid to infiltrate the ceramic skeleton to obtain a layered structure (TiC+Ti) / Mg composite material.

2. The preparation method according to claim 1, characterized in that: The total volume of the TiH2 powder and graphite powder described in step (1) accounts for 20%-50% of the total volume of the slurry, the ammonium polyacrylate accounts for 1%-1.5% of the total volume of the slurry, and the neutral silica sol accounts for 0.8%-1% of the total volume of the slurry.

3. The preparation method according to claim 1, characterized in that: The specific steps of step (4) are as follows: first, the green body after low-temperature drying is placed in a vacuum sintering furnace, and then the air in the sintering furnace is extracted. When the vacuum gauge value reaches below -0.1 MPa, an inert gas with a purity of 99.9% is continuously introduced into the vacuum furnace, and the vacuum gauge value is maintained at 0 MPa. Normal pressure sintering is performed, and the temperature is increased at a rate of 8-12 ° C / min, and the temperature is kept at 500 ° C for 25-35 minutes, 1000 ° C for 0.8-1.2 hours, and 1500 ° C for 1-1.5 hours. Finally, the temperature is reduced to 200 ° C at a cooling rate of 8-12 ° C / min and then cooled in the furnace to obtain a layered (TiC+Ti) porous ceramic skeleton.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the layered (TiC+Ti) porous ceramic skeleton to the magnesium alloy in step (5) is 3:7-8.

5. The (TiC+Ti) / Mg layered composite material prepared by the preparation method according to claim 1.

6. Use of the (TiC+Ti) / Mg layered composite material according to claim 5 in the fields of aerospace, automobile or communication.

Citation Information

Patent Citations

  • High-volume-fraction ceramic-metal layered composite material and preparation method thereof

    CN107326211A

  • Preparation method of carbide in-situ reinforcement titanium and alloy porous scaffold

    CN109940162A